Pengaruh Kinerja Lingkungan, Struktur Modal, dan Kepemilikan Manajerial terhadap Nilai Perusahaan pada Perusahaan Sektor Energi Bursa Efek Indonesia Tahun 2022-2024 - Rafly Fachrorroji; Hermi Hermi (Anggaran : Jurnal Publikasi Ekonomi dan Akuntansi, 2025)
This study aims to examine the relationship between a company's value (firm value) and three key variables: environmental performance, capital structure, and management ownership. The research focuses on companies listed on the Indonesia Stock Exchange during the period from 2022 to 2024. The objective is to understand how these internal and external factors contribute to shaping a company’s market valuation and overall financial health. Using a panel data regression analysis with a fixed effect model, the study provides empirical evidence based on secondary data drawn from company financial reports and sustainability disclosures. The results indicate that capital structure, measured by the proportion of debt to equity, has a significant negative impact on firm value. In contrast, both environmental performance and the proportion of shares owned by management have a positive and significant effect on firm value. These findings suggest that while excessive debt may erode investor confidence and reduce a firm's valuation, strong environmental commitments and management ownership foster positive perceptions in the eyes of stakeholders, including investors and customers. Theoretically, this research supports stakeholder and agency theories by highlighting how internal governance and ethical responsibility play a role in corporate success. Pragmatically, the results offer important insights for companies, especially in emerging markets like Indonesia, to align sustainability and ownership strategies with financial management to boost firm value. Companies are encouraged to optimize their capital structures, strengthen their environmental reporting practices, and promote management ownership as a way to align interests and enhance long-term performance. Overall, this study contributes to the literature on corporate governance and sustainability by providing current, context-specific evidence relevant to stakeholders in the Indonesian capital market.